2016
DOI: 10.5194/acp-2016-888
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comparison of Emissions Inventories of Anthropogenic Air Pollutants in China

Abstract: <p><strong>Abstract.</strong> Anthropogenic air pollutant emissions have been increasing rapidly in China. Modelers use emissions inventories to assess temporal and spatial distribution of these emissions to estimate their impacts on regional and global air quality. However, large uncertainties exist in emissions estimates and assessing discrepancies in these inventories is essential for better understanding of the trends in air pollution over China. We compare five di… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…This is similar to the results of previous studies that compared the emissions of other air pollutants between inventories. Saikawa et al 8 compared the emissions of air pollutants (CO, SO 2 , NO x , and PM 10 ) from China among five inventories and revealed that the discrepancies for each sector were larger than those for the total emissions. Li et al 9 showed that differences at the sectorial level were higher than those of the total estimates by comparing SO 2 and NO x emissions over China in the ECLIPSE and MIX inventories.…”
Section: Comparisons Of Six Bottom-up Inventoriesmentioning
confidence: 99%
See 1 more Smart Citation
“…This is similar to the results of previous studies that compared the emissions of other air pollutants between inventories. Saikawa et al 8 compared the emissions of air pollutants (CO, SO 2 , NO x , and PM 10 ) from China among five inventories and revealed that the discrepancies for each sector were larger than those for the total emissions. Li et al 9 showed that differences at the sectorial level were higher than those of the total estimates by comparing SO 2 and NO x emissions over China in the ECLIPSE and MIX inventories.…”
Section: Comparisons Of Six Bottom-up Inventoriesmentioning
confidence: 99%
“…However, differences among emission inventories and how the variations affect model simulations have not been investigated well. Recently, comparisons between emission inventories have been conducted for the emissions of air pollutants such as NO x , SO 2 , CO, and PM 10 from China [8][9][10] , but BC was not examined in these Page 2 of 37 Environmental Science: Atmospheres Environmental Science: Atmospheres Accepted Manuscript 3 studies. Kondo et al 11 evaluated BC emissions from China using CTMs and BC measurements at Cape Hedo on Okinawa Island in the East China Sea.…”
Section: Introductionmentioning
confidence: 99%
“…The inventory contains monthly emissions of pollutants from different source categories. Saikawa et al (2016) compared the major features of different anthropogenic emission inventories for China. Detailed information regarding these inventories can be found in the publications presenting them.…”
Section: Anthropogenic Emissionsmentioning
confidence: 99%
“…This technique has been widely used in the climate predictions (Murphy et al, 2004;Tebaldi and Knutti, 2007), and recently adopted in air quality predictions (Delle Monache et al, 2006;Huijnen et al, 2010). A recent study has compared a few anthropogenic emission inventories in China during 2000(Saikawa et al, 2016, but detailed evaluation of air quality model results based on these inventories for over an extended time period have not been performed. The methods to utilize the strength of different emission inventories to get improved air quality predictions for China have not been reported in the literature.…”
Section: Introductionmentioning
confidence: 99%